Government's Strategy and Role in the Internationalization of MSMEs - Abdul Halim; Imam Mukhlis (Green Publisher Indonesia, 2022)
This study aims to discuss the strategy and role of the government in the internationalization of MSMEs. The research method used in this study is a qualitative descriptive method. The type of data used in this research is qualitative data, which is divided into primary data and secondary data. Sources of data obtained through library research techniques that refer to resources available online and offline, such as: scientific journals, books, and news from trusted sources. The results showed that the internationalization strategy conceptually and theoretically can be divided into two categories, namely internationalization theory and selectivity theory. The emergence of internalization theory can threaten the existence of MSMEs due to the development of large companies in the 1970s. Furthermore, in its development, the theory seeks to internalize the benefits that can be obtained from internationalization, localization, and ownership. At the same time, the eclectic theory in the internationalization strategy places more emphasis on the resources owned by MSMEs and knowledge of the markets and networks that MSMEs choose to market their products. The steps taken by the current government by creating a special portal at INSW are appropriate, but if this is achieved not only through existing portals, but also through direct engagement with business people, including through seminars and workshops by interacting with them more often and socialize.